Subjects Barbarian, Monstrous, and Wild Encounters in the Arts and Contemporary Politics - Boletsi, Maria (Thamyris/Intersecting: Place, Sex and Race Series, 2017)
In a contemporary political climate where barbarians, monsters, and savages have become ubiquitous figures of otherness, Subjects Barbarian, Monstrous, and Wild gathers essays which explore both the oppressive, dispossessing functions and subversive potentials of these figures in and through art and literature